Perancangan Sistem Informasi Jemaat Dan Warta Jemaat Menggunakan Whatsapp Gateway - Malau, Emerson P; Simanjorang , Steffanny Putri Nelan (UNIKA Santo Thomas, 2023)
HKBP Ressort Sidikalang II which is one of the church ministry institutions. In the process of collecting data on the congregation, it is still done manually, as well as the means of disseminating Church information, namely the Church News. The delivery of news in this church is also still manual, meaning that when a reporter or congregation wants to convey information, he must directly meet with the church administrator. This kind of information medium makes it difficult for congregations to obtain church information, as well as makes it difficult for church assemblies to work. The author takes advantage of the current development of information technology, namely using the WhatsApp application. The author will design an Information System Using WhatsApp Gateway that can help the process of processing web-based church data. This website is useful for providing information on congregational data and church leadership assemblies that can be accessed more easily